Economic and Welfare Effects of investing Oil Revenue in the Iranian Economy: A Recursive Dynamic Computable General Equilibrium(CGE) Approach - javad khajehtorab; sharareh majdzadeh tabatabaei; seyednematollah mosavi (Pizhūhishnāmah-i Iqtiṣād-i Inirzhī-i Īrān, 2019)
In the present study, the approach of a recursive dynamic computable general equilibrium was used in order to simulate the economic and welfare effects of the allocation of oil revenues in the Iranian economy. Accordingly, changes in the production index of different economic sectors, changes in consumption and price levels in the form of 4 scenarios of different combinations of depositing oil revenues to the National Development Fund of Iran, and using the social accounting matrix (SAM) related to the year 2011 were considered. The results showed that by using different scenarios of oil revenue allocation, the highest growth of production and consumption of the studied sectors compared to the basic scenario of the fourth scenario (save 20% of oil revenues in the country's foreign exchange fund and invest 30% of the fund's resources in the industry) will be. Meanwhile, the highest rate of price reduction in the production sector is related to the fact that 20% of oil revenues are saved in the country's foreign exchange fund and no amount has been invested in the economic sectors. In fact, the increase in production and boom is due to the increase in investment in the industrial sector of inflation and will lead to the growth of prices of manufactured products. Therefore, by allocating the fund's resources in the industrial sector, the goal of economic growth and increasing household welfare will be achieved. In fact, due to the strong links between the industrial sector and other sectors, including agriculture and services, by investing to improve the productivity of the industrial sector, all economic sectors have benefited from this issue and by increasing production while growing demand for investment and increasing household consumption will bring greater welfare to consumers.